Efforts to Increase Literacy through the Reading Guide Method for Class 2 Students at SDN Kraton 5 Bangkalan - Nurhandayany; Maulidina, Eristya; Rahman, M. Saufi (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2025)
In the learning process in class there are obstacles when literacy activities are implemented, namely students get bored with reading activities because they are too monotonous so students play more and Talk to his friends. The aim of this research is to improve the literacy skills of grade 2 students at SDN Kraton 5 Bangkalan with a total of 35 students using the reading guide learning method.This research uses a descriptive analysis study. Research stages include collecting data, processing data, describing data and interpreting data and concluding data.The research was conducted over two meetings, namely on Saturday, March 9 2024 and on Saturday March 23, 2024. This research was carried out through observation, interviews, tests and documentation. The results of the research show that the application of the reading guide learning method can improve The literacy skills of students in the Indonesian language subject